Estudo da nota fiscal eletrônica como instrumento da governança eletrônica: perspectiva dos auditores fiscais da Secretaria da Fazenda do Estado do Ceará - Moreira, Cibele Marques (2014)
Over the last few years, the State has been changing its way of dealing with citizens, especially due to the new Information and Communication Technologies (ICTs) which added to government functions provided benefits and improvements in public administration,characterizing the so-called electronic governance. The Electronic Invoice (e-Invoice) was established according to theassumptions of electronic governance because it used the available technology to modernize public administration tax and benefit all those involved with in it. In this context, the general aim of this paper is to analyze the consequences resulting from the use of e-Invoice, under the opticsof electronic governance, from the perspective of tax auditors of the Department of Finance of the State of Ceará, known as SEFAZ-CE. In order to achieve this purpose, four specific objectives were defined. First, it was identified the level of SEFAZ-CE tax auditors´knowledge pertinent to the topic about the electronic governance and electronic government issues. Then,the perceptionsof SEFAZ-CE tax auditors about the use of e-Invoice for taxpayers, for society and for tax administrations were analised. The literature review, required for the construction of the theoretical framework that provided the basis of this paperwere the subjects of governance in Public Administration; electronic governancein one of its dimensions, electronic government; and e-Invoice. The methodology used in the research included conducting a single case study at SEFAZ-CE, and adopting a self-administered questionnaire as a tool for collecting data from the individuals surveyed. With the results, it was concluded that SEFAZ-CE tax auditors have held a good level of knowledge on the subject of the research; their perceptions on it is that the use of e-Invoice broughtimpacts to taxpayerswhich have shaped the practiceof electronic governance related to reduction of transaction costs and citizen participation or social integration; the use of e-Invoice impacted widely and positively, the whole society; and, with respect to tax administration, the practices of electronic governance noted wereincreasing efficiency and interaction between governments.